PENERAPAN PERHITUNGAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE FULL COSTING PADA XYZ - Safri Safri (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACTThis study aims to calculate the cost of goods manufactured that is relevant to PT XYZ's business, so that it is equivalent to each unit produced. from research conducted by applying the calculation of the full costing method, the difference is 40.27% with a nominal value of Rp. 45,426,500. From the results of these studies it can be seen that there are very large differences in terms of percentages and nominal values, management analysis may give a wrong picture if using the existing literature. Even though the final results of the financial statements present the same nominal value, in practice management will have problems in calculating the gross profit analysis and for the manufacturing accounting recording system that the company already has, its use is better maximized, so that the company's production cycle can provide information that the company is active effectively and efficiently. Keywords: Cost of goods manufactured, Full costing method, Manufacturing accounting recording system